Unused medication waste: respondent’s opinion from current study in Malaysia - Islam, Mohd Aminul; Azad, Abul Kalam; Sunzida, Nushrat Khan (Wolters Kluwer Medknow, 2018)
There are a lot of efforts have been employed to find out the major factor which increase the volume of medication waste. However, several survey reports were highlighted the key factors of medication waste like lack of knowledge on the serious impact of unused medication waste, neglected the proper disposal technique, not following the drug take bag system, pharmacy or dispensaries were not providing proper guideline or any materials to return unused medicines to the pharmacy, not enough campaign or community activities on medication waste, educational institute were not taking any responsibility like institution base extra seminar or lecturer on dangerous environmental impact and serious public health problem due to unused medications. However, this report will be encouraged to the government policy maker, social and welfare department and health facilities department to take an emergency necessary steps to reduce or resolved this problem.